The longitudinal relationship between school climate and Internet gaming addiction among Chinese children: a moderated mediation model - Wei, Chang; Xu, Qian (Frontiers in Psychiatry, 2025)
IntroductionSchool climate is associated with children’s Internet gaming addiction; however, the mechanisms underlying this association have been largely unexplored. Based on the ecological systems theory, the social learning theory, and the diathesis-stress model, we examined the association between school climate and children’s Internet gaming addiction, as well as the mediating role of deviant peer affiliation and the moderating role of sensation seeking in this relationship.MethodsThe study involved 419 Chinese children participating in a two-wave longitudinal investigation conducted over the course of one year. Among the participants, 54.4% were boys and 45.6% were girls. The mean age of the participants at Wave 1 was 10.70 years (SD = 0.58). We used SPSS 27.0 to generate descriptive statistics and correlations. We adopted Model 4 of the PROCESS for SPSS to examine the mediation model. We used Model 14 of the PROCESS for SPSS to examine the moderated mediation models.ResultsThe results showed that school climate was negatively correlated with Internet gaming addiction among children one year later. Deviant peer affiliation mediated the pathway from school climate to Internet gaming addiction, and this mediating pathway was moderated by sensation seeking.ConclusionThese findings demonstrated the individual differences in the association between school climate and Internet gaming addiction, which has implications for the prevention of Internet gaming addiction among children.